PROBLEMS OF COMPETITION THEORY AND POLICY IN THE ORDOLIBERAL THOUGHT - Moszyński, Michał (Ekonomia i Prawo. Economics and Law, 2013)
The study is devoted to the ordoliberal concepts of economic order based on competition. Firstly the historical background of ordoliberal economic thought is sketched and the views of the most important authors on mechanism of competition and its institutional foundations are introduced. Next the elements of economic order of the Federal Republic of Germany are depicted. The considerations are based on the assumption that ordoliberalism still offers an interesting proposal for intellectual reflection and for the theory of economic policy, particularly in the area of creating effective institutional framework for market processes.